Evaluation of homeopathy in seed germination of yellow ipe - Silva, Naira Maranhão (2014)
Studies with homeopathie on seed germination of native forest species are scarce, regardless of its potential as low impact technology. Therefore, the objective of this study was to evaluate the use of homeopathic medications in different dynamizations in the seed germination of yellow ipe. The experimental design was completely randomized with three replications, in a factorial scheme with the three medicines in five dynamizations, totaling 16 treatments with the control consisting of distilled water. The medications used were Calcarea carbonica, Carbo vegetabilis and Silicea. The mediations were applied in of 6, 12, 30, 100 and 200 centesimals hahnemanianas (CH) dynamizations. Regarding germination percentage and speed of germination index the medicament Silicea in 12CH dynamization was less efficient when compared to others medications and dynamizations. The use of homeopathic preparations does not benefit the pattern of yellow ipe seeds germination.